107k views
1 vote
PLssss answer
Which expression below gives the average rate of change of k on -3 ≤ x ≤ 5 ?

PLssss answer Which expression below gives the average rate of change of k on -3 ≤ x-example-1

1 Answer

4 votes

Answer:

ave rate of change = k(5) - k(-3)

----------------

5+3

Explanation:

To find the average rate of change

ave rate of change = f(x2) - f(x1)

----------------

x2-x1

We know that x2 = 5 and x1 = -3

ave rate of change = k(5) - k(-3)

----------------

5--3

ave rate of change = k(5) - k(-3)

----------------

5+3

User Xielingyun
by
5.4k points